2014
DOI: 10.1002/arch.21153
|View full text |Cite
|
Sign up to set email alerts
|

CARBOHYDRASES IN THE DIGESTIVE SYSTEM OF THE SPINED SOLDIER BUG, Podisus maculiventris (SAY) (HEMIPTERA: PENTATOMIDAE)

Abstract: The spined soldier bug, Podisus maculiventris, is a generalist predator of insects and has been used in biological control. However, information on the digestion of food in this insect is lacking. Therefore, we have studied the digestive system in P. maculiventris, and further characterized carbohydrases in the digestive tract. The midgut of all developmental stages was composed of anterior, median, and posterior regions. The volumes of the anterior midgut decreased and the median midgut increased in older ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(64 reference statements)
0
8
0
2
Order By: Relevance
“…() investigated the inhibitory potential of acarbose on some bruchid beetles and several species of parasitic wasps, and found a greater ability of acarbose to inhibit α‐amylase activity compared to α‐amylase inhibitor taken from wheat. High sensitivity of amylase from the bruchid Zabrotes subfasciatus (Boheman) (Grossi de Sa et al., ), the bug Podisus maculiventris (Say) (Ghamari et al., ), and the weevil Sitophilus zeamais Motschulsky (Lopes et al., ) to the inhibitor has been also reported. In our previous study we found high inhibitory potential of acarbose on α‐amylase activity, as well as effects of acarbose on weight, size, and physiological and biological parameters of P. interpunctella (Masoumzadeh et al., ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…() investigated the inhibitory potential of acarbose on some bruchid beetles and several species of parasitic wasps, and found a greater ability of acarbose to inhibit α‐amylase activity compared to α‐amylase inhibitor taken from wheat. High sensitivity of amylase from the bruchid Zabrotes subfasciatus (Boheman) (Grossi de Sa et al., ), the bug Podisus maculiventris (Say) (Ghamari et al., ), and the weevil Sitophilus zeamais Motschulsky (Lopes et al., ) to the inhibitor has been also reported. In our previous study we found high inhibitory potential of acarbose on α‐amylase activity, as well as effects of acarbose on weight, size, and physiological and biological parameters of P. interpunctella (Masoumzadeh et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…Impacts of pH were determined according to Ghamari et al. () with slight modifications. The effect of pH was determined with a universal buffer (40 mM citrate‐phosphate‐borate, pH 3‐8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…растительноядных насекомых, α-амилазы входят в число наиболее важных пищеварительных гидролаз (Da Lage, 2018). У насекомых, включая клопов, как и у других животных, геном, как правило, содержит несколько вариантов генов α-амилаз, что предположительно расширяет возможности утилизации разных форм крахмала в различных условиях (Da Lage et al, 2002;Da Lage, 2018;Ghamari et al, 2014). В целом, α-амилазы насекомых по структуре близки α-амилазам других животных и объединены в подсемейство гликозилгидролаз GH13_15 совместно с аналогичными ферментами других беспозвоночных (Stam et al, 2006).…”
Section: α-амилазыunclassified